Production of citric acid from empty fruit bunches through solid state bioconversion by using rotary drum bioreactor with Aspergillus niger - Bari, Md. Niamul; Alam, Md. Zahangir; Jamal, Parveen; Al-Mamun, Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The study for the production of citric acid from oil palm empty fruit bunches (EFB) by solid state bioconversion in rotary drum bioreactor using locally isolated Aspergillus niger was conducted. The optimum media content, process conditions, particle size of EFB and its distribution and bioconversion period were adopted from laboratory scale production experiments. The highest production of citric acid of 327.67±3.7 g/kg-EFB was obtained in rotary drum bioreactor with the continuous supply of saturated air of 8.4 L/min (2.8 L/kg/min) and the agitation of 90 rotation/day. The findings of the present study might contribute to the economic development by encouraging for proper management of oil palm industry biomass as well as other lignocellulosic residues.